The Urgency of Using YouTube Channels as Loan Collateral: Orientation and Limitations from a Progressive Legal Perspective: Urgensi Penggunaan Channel YouTube Sebagai Jaminan Utang: Orientasi dan Limitasi dalam Persepektif Hukum Progresif. - Bagenda, Christina; Carbonilla, Cicilia Hellena (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents a comprehensive analysis of the legal regulations and progressive legal aspects associated with using YouTube channels as collateral in Indonesian businesses. In the digital era, the complexity of relevant laws and regulations necessitates a progressive legal approach to accommodate digital assets, copyright protection, and personal data security while considering their impact on business transactions. The primary objective of this research is to examine the legal framework concerning the use of YouTube channels as collateral in Indonesia. Employing a normative legal research methodology and a legislative and conceptual approach, this study delves into the legal framework. The source materials include legislation, court decisions, legal literature, and scholarly articles, utilizing in-depth document analysis for data collection and analysis. The results of this research shed light on the multifaceted legal regulations governing the utilization of YouTube channels as collateral, encompassing legislation, copyright protection, consumer rights, and social media regulations, emphasizing the importance of understanding rights and responsibilities, and consulting legal experts. From a progressive legal perspective, the use of YouTube channels as collateral mirrors the legal adaptation to digital assets, acknowledging their economic value but requiring careful consideration of limitations such as fluctuating digital asset value, ownership changes, copyright, and data privacy. The significance of individual rights, copyright protection, and data privacy must be safeguarded within progressive legal regulations. This study contributes to the legal discourse on digital asset usage in Indonesia, offering insights into the evolving legal landscape and its implications for digital business transactions and asset management. Highlights: Legal Complexity: The study explores the intricate legal landscape governing the use of YouTube channels as collateral in digital business transactions. Progressive Legal Adaptation: It highlights the need for progressive legal approaches to accommodate digital assets, copyright protection, and data privacy in the digital era. Rights Safeguarding: The research emphasizes the importance of upholding individual rights, copyright protection, and data privacy within the legal framework for digital collateral use. Keywords: YouTube Collateral, Legal Framework, Digital Business, Copyright Protection, Data Privacy